2017
DOI: 10.1007/s00402-017-2671-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes of posterior condylar offset results in midflexion instability in single-radius total knee arthroplasty

Abstract: Whereas the joint line can be displaced by up to 5 mm without measurable changes in joint stability, reconstruction of the posterior offset within a tight range of 2 mm is necessary to avoid midflexion instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 19 publications
0
24
0
1
Order By: Relevance
“…This already results in a different effect on the flexion gap; however, it was possible to see that the reduction of the tibial slope leads to larger posterior femoral resection in all cases to achieve the desired gap width. In this context, it has to be mentioned that reduction of posterior condylar offset (PCO) is critical for flexion ability and resulting stability of the knee [ 25 , 29 ]. Thus, the maximum posterior resection is now set to 9 mm in the algorithm, as Matziolis et al.…”
Section: Discussion and Current Evidencementioning
confidence: 99%
“…This already results in a different effect on the flexion gap; however, it was possible to see that the reduction of the tibial slope leads to larger posterior femoral resection in all cases to achieve the desired gap width. In this context, it has to be mentioned that reduction of posterior condylar offset (PCO) is critical for flexion ability and resulting stability of the knee [ 25 , 29 ]. Thus, the maximum posterior resection is now set to 9 mm in the algorithm, as Matziolis et al.…”
Section: Discussion and Current Evidencementioning
confidence: 99%
“…To the best of our knowledge, only one such study exists, which reported that JLE of up to 5 mm has no influence on stability at midflexion. 45 An interesting observation is that the same study reported that altering the posterior condylar offset had a profound effect on MFI. This is a point worth considering, as changing the posterior condylar offset has been associated with MFI in several other papers including the seminal article by Martin and Whiteside.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, anterior translation of the femoral component may have a more important role in laxity than proximalization. This is suggested in an in vivo study by Matziolis et al 45 Here the authors retrospectively looked at 42 PS SR TKRs and noted that altering the posterior condylar offset by more than 2 mm led to MFI in 44% of cases, whereas displacing the joint line up to 5mm had no influence on stability in midflexion.…”
Section: Elevation Of Joint Linementioning
confidence: 85%
See 1 more Smart Citation
“…2). Ein Verlust an posteriorem Kondylenoffset bedingt ein reduziertes femorales Rollback und kompromittiert damit die Beugefähigkeit und Stabilität [16,17]. Da trotz der angesprochenen Radiendifferenzen die konkreten Unterschiede der Femurgeometrien letztendlich im Millimeterbereich liegen, ist aufseiten des Femurs die akkurate Operationstechnik von entscheidenderer Bedeutung als das vorliegende Implantatdesign anzusehen.…”
Section: Introductionunclassified